Development of Drinking Water Supply Service in Purworejo District - Lia Kurnia Putri; Adhi Yuniarto (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Water Supply Company (PDAM) in Purworejo District is a responsible instituation in serving and fulfilling the need of clean water for the local people in Purworejo. The current service coverage of the Water Supply Company in Purworejo was 52.60%. Water Supply Company in Purworejo unit had served 14 urban villages and had 5 planned development villages. However, out of 19 urban villages, the clean water distribution network system was not evenly distributed to customers and the amount of water loss was quite high. To overcome these problems, it was necessary to do an analysis and development plan for the clean water distribution network system. The application used to analyze the existing conditions and the development was the Epanet 2.0 application. The results of the existing condition analysis showed that running was not successful. The planning period will be carried out in 2018 until 2037 which is divided into 2 stages, namely year (2018-2027) and year (2028-2037). The planning was done by calculating projections of the population and public facilities to determine water requirements. The results of the development plan analysis showed that there were 2 additional blocks in stage 2 so that the total blocks formed were 24 blocks. The pipeline repairs carried out are also divided into 2 stages, namely in 2021 and in 2026. This is meant to reduce the planning costs, because the development budget used will also be divided into 2 stages.